Natural and territorial heritage. From Protection to the Management and Regeneration of the Cultural Landscape - Capel, Horacio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
Heritage protection initially concerned monuments with significant historical and artistic value, but was subsequently extended to encompass historic buildings in towns and cities. Later on, it was extended further still to cover territory and landscape as well as immaterial and intangible aspects. This broader remit poses many problems, not least how to manage heritage.Two developments in the concept of heritage are connected with the natural environment on the one hand and with the territory and landscape on the other. The creation of national parks and the extension of heritage to encompass agriculture and rural space have had a decisive impact in this respect.